2017
DOI: 10.1002/er.3836
|View full text |Cite
|
Sign up to set email alerts
|

Oxy-fuel combustion characteristics and kinetics of microalgae and its mixture with rice straw using thermogravimetric analysis

Abstract: Summary The thermal behavior of rice straw, microalgae, and their mixture was studied by thermogravimetric analysis (TGA). Co‐combustion of rice straw and microalgae broadened the temperature range of combustion, facilitated ignition, and promoted burnout. The blend ratio of microalgae should be less than or equal to 10% in a 20%O2/80%N2 atmosphere and 30% in a 20%O2/80%CO2 atmosphere to reach a higher comprehensive combustion index (CCI) value than the individual fuels. The co‐combustion with a small ratio of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…More researches about biomass were conducted by thermogravimetry tests to study the combustion characteristics, pollutant emissions, kinetics, and co‐firing characteristics with other substances (coal or sewage sludge) in different atmospheres (O 2 /CO 2 or O 2 /N 2 ) . Some studies are about the burning of micron‐sized biomass particles.…”
Section: Introductionmentioning
confidence: 99%
“…More researches about biomass were conducted by thermogravimetry tests to study the combustion characteristics, pollutant emissions, kinetics, and co‐firing characteristics with other substances (coal or sewage sludge) in different atmospheres (O 2 /CO 2 or O 2 /N 2 ) . Some studies are about the burning of micron‐sized biomass particles.…”
Section: Introductionmentioning
confidence: 99%
“…Typical TGA advantages are accurate real-time sample mass measurements, high reproducibility, and well-defined temperature and gas-phase conditions [7][8][9]. TGA has been applied in recent years to the study of sewage sludge, rice straw, woody biomass, plastics, and other organic waste thermal characteristics using simulated pyrolysis conditions [6,[10][11][12][13]. TGA is coupled with spectrometers, such as Fourier transform infrared spectroscopy (FTIR), to analyze the temporal resolution of specific gas-phase fragments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been thought that variances in the organic and mineral compounds in the typical species of microalgae lead to differences in thermal degradation. However, studies on the co-combustion of Scenedesmus almeriensis and lignocellulosic biomass [ 31 ], Chlorella vulgaris and textile dyeing sludge [ 33 ], and Chlorella protothecoides and rice straw [ 34 ] have found that a material's composition does have an effect on its combustion performance. To date, the co-combustion of microalgae and solid waste has not been performed, with the exception of Chlorella protothecoides and municipal solid waste under N 2 /O 2 and CO 2 /O 2 atmospheres [ 35 ].…”
Section: Introductionmentioning
confidence: 99%